2021
DOI: 10.1002/edm2.314
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of Chinese patent medicines containing red yeast rice on hyperlipidaemia: A network meta‐analysis of randomized controlled trials

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…The effect of RYR was similar to that of low-intensity/low-dose statins on LDL-C (MD 0.03 mmol/L; 95% CI −0.36, 0.41 [ p = 0.89]) and TC (MD −0.05 mmol/L; 95% CI −0.28, 0.18 [ p = 0.67]) [ 10 ]. Finally, a network meta-analysis of 47 randomized controlled trials involving 4824 subjects, evaluating three different Chinese RYR supplements (most commonly Xuezhikang 600 mg twice daily), showed that RYR significantly reduced LDL-C, TC, and triglycerides versus placebo [ 67 ]. No significant differences in the levels of these parameters were observed with RYR versus simvastatin, although a ranking analysis suggested that Xuezhikang (surface under the cumulative ranking [SUCRA] value 82.6%) was more likely than simvastatin (SUCRA value 74.9%) to be effective in reducing LDL-C [ 67 ].…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
“…The effect of RYR was similar to that of low-intensity/low-dose statins on LDL-C (MD 0.03 mmol/L; 95% CI −0.36, 0.41 [ p = 0.89]) and TC (MD −0.05 mmol/L; 95% CI −0.28, 0.18 [ p = 0.67]) [ 10 ]. Finally, a network meta-analysis of 47 randomized controlled trials involving 4824 subjects, evaluating three different Chinese RYR supplements (most commonly Xuezhikang 600 mg twice daily), showed that RYR significantly reduced LDL-C, TC, and triglycerides versus placebo [ 67 ]. No significant differences in the levels of these parameters were observed with RYR versus simvastatin, although a ranking analysis suggested that Xuezhikang (surface under the cumulative ranking [SUCRA] value 82.6%) was more likely than simvastatin (SUCRA value 74.9%) to be effective in reducing LDL-C [ 67 ].…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
“…Many available studies have evaluated the efficacy of RYR preparations on lipid profiles, and (to a lesser extent) CVD outcomes. The results of such studies have been summarised in several meta-analyses [18,21,22]. Beneficial effects of RYR supplementation on plasma lipid profile have been recognised for several years.…”
Section: Efficacy Of Red-yeast Rice In Dyslipidaemias and Cardiovascu...mentioning
confidence: 99%
“…However, the authors did suggest that owing to limitations inherent in their study, the validity of their results should be confirmed in large, well-designed, multicentre, prospective RCTs. [22].…”
Section: Efficacy Of Red-yeast Rice In Dyslipidaemias and Cardiovascu...mentioning
confidence: 99%
“…ZBT has the functions of regulating lipid, stabilizing carotid plaque, improving vascular endothelial function and so on, and has few side effects (Su and Hu, 2021). Several clinical studies have shown that ZBT has a good lipid-lowering effect (Xu et al, 2010;Zhao et al, 2017;Xu et al, 2018;Xu et al, 2022). In a mouse model, ZBT can affect the MAPK-ERK-TLRs pathway by down-regulating the expressions of TLR4 and P-ERK1/2 proteins, it can inhibit the transduction of inflammatory signaling pathway, prevent the occurrence and development of inflammation, regulate blood lipids, and antagonize insulin resistance to protect the liver (Liao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%